2022
DOI: 10.1155/2022/6570879
|View full text |Cite
|
Sign up to set email alerts
|

IPO5 Mediates EMT and Promotes Esophageal Cancer Development through the RAS-ERK Pathway

Abstract: Objective. In the development of many tumors, IPO5, as a member of the nuclear transporter family, exerts a significant function. Also, IPO5 is used as a therapeutic target for tumors based on some reports. By studying IPO5 expression in esophageal cancer tissues, the mechanism associated with IPO5 improving esophageal cancer development was explored in this study. Methods. To gain differentially expressed genes, this study utilized mRNA microarray and TCGA database for comprehensive analysis of esophageal can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Current studies have confirmed that MMP7 promotes the malignant progression of esophageal cancer, colon cancer, and prostate cancer. [33][34][35] Wang et al confirmed through research that the knockout of BCAR4 inhibits the generation of MMP7 by increasing the expression of miR-227, thereby delaying the pathological process of glioma. [36] And MMP7 was found to be one of the targets of miR-227 by fluorescein analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have confirmed that MMP7 promotes the malignant progression of esophageal cancer, colon cancer, and prostate cancer. [33][34][35] Wang et al confirmed through research that the knockout of BCAR4 inhibits the generation of MMP7 by increasing the expression of miR-227, thereby delaying the pathological process of glioma. [36] And MMP7 was found to be one of the targets of miR-227 by fluorescein analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the nuclear transport system, therefore, has future potential for therapeutic intervention and could contribute to the elucidation of disease mechanisms. IPO5 gene also seems to play an important role in the metastatic process via matrix metalloproteinase 7 ( MMP7 ) regulation ( 66 ) and EMT induction ( 67 ). Furthermore, IPO5 expression may affect the tumor immune microenvironment and mediate tumor immune response ( 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is a crucial process that cancer cells exploit for metastasis by transition of their epithelial phenotype into a mesenchymal phenotype. Previous research studies have confirmed that EMT not only participates in the carcinogenesis and progression of malignancies but also plays a unique role in cancer metastasis and chemorefractoriness [3][4][5]. In vitro analysis of an immunodeficient mouse model also indicated EMT was involved in the regulation of tumors, which greatly enhanced tumor cell self-renewal and differentiation [6][7][8].…”
Section: Introductionmentioning
confidence: 89%